2010
DOI: 10.1016/j.juro.2010.03.127
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Methodological Quality of Systematic Reviews Published in the Urological Literature From 1998 to 2008

Abstract: Results suggest that an increasing number of systematic reviews are published in the urological literature. However, many systematic reviews fail to meet established methodological standards, raising concerns about validity. Increased efforts are indicated to promote quality standards for performing systematic reviews among the authors and readership of the urological literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
32
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 25 publications
7
32
0
2
Order By: Relevance
“…Although the more rigorous the review methods used and the higher the quality of the primary research that is synthesized in SRs, which involve searching for, selecting, critically appraising, and summarizing the results of primary research (Cook et al, 1997), not all SRs were of high quality and the evidence that it produced were not at high level. This is consentient with the results of other studies, which showed that many SRs fail to meet established methodological standards, raising concerns about validity (MacDonald et al, 2010), or seem to have serious methodological flaws leading to a high risk of bias (Lundh et al, 2009). Not only methodological quality problems, but also reporting quality problems existed.…”
Section: Discussionmentioning
confidence: 65%
“…Although the more rigorous the review methods used and the higher the quality of the primary research that is synthesized in SRs, which involve searching for, selecting, critically appraising, and summarizing the results of primary research (Cook et al, 1997), not all SRs were of high quality and the evidence that it produced were not at high level. This is consentient with the results of other studies, which showed that many SRs fail to meet established methodological standards, raising concerns about validity (MacDonald et al, 2010), or seem to have serious methodological flaws leading to a high risk of bias (Lundh et al, 2009). Not only methodological quality problems, but also reporting quality problems existed.…”
Section: Discussionmentioning
confidence: 65%
“…Resultados parecidos com este foram encontrados em uma avaliação das RS na área da Medicina Veterinária, indicando poucos estudos com alta qualidade metodológica (Faggion Jr., Listl, & Giannakopoulos, 2012). Soma-se a isso a constatação de que, com o passar dos anos, as RS não têm apresentado um aprimoramento significativo de qualidade que acompanhe a crescente quantidade de publicações (MacDonald, Canfield, Fesperman, & Dahm, 2010).…”
unclassified
“…외국의 경우 1990년대부터 메타분석 연구의 질 평가를 꾸준히 수행해 왔다 [6][7][8][9][10][11][12]. 하지만 국내의 경우 거의 이루어 지지 않았으며 선행 연구에 의하면 체계적인 연구의 질 평가 도구 의 사용 없이 연구특성만을 서술하여 경영학 분야의 메타분석 연 구의 현황을 보고한 연구 [13], 연구자가 고안한 평가내용으로 국내 메타분석 연구의 방법론적 고찰을 수행한 연구 [14], APA 평가도구 를 사용하여 특수교육 분야의 메타분석 연구의 질을 평가한 연구 Meta-analysis [15], QUOROM (Quality of Reporting of Meta-analyses) [5], MOOSE (Meta-analysis of Observation Studies in Epidemiology) [16], PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analysis) [17], OQAQ (The Overview Quality Assessment Questionnaire) [18], AMSTAR (Assessment of Multiple Systematic Reviews) [19,20] 등을 주로 사용하여 메타분석 연구의 질 평가를 수행해 왔 다 [13][14][15][16][17][18][19].…”
unclassified